Markerless versus marker-based motion capture - a comparision of measured joint centres - Steele, K.; Corazza, S.; Scanlan, S.; Sheets, A.; Andriacchi, T. P. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Markerless motion capture (MMC) techniques have recently been introduced as a viable alternative to traditional marker-based methods used for capturing motion and performing biomechanical analyses (Corazza, 2006, Mündermann, 2006). Since both methods attempt to measure underlying bone motion, calculated joint center (JC) locations should be similar. Traditional marker-based methods such as the point-cluster technique (PCT, Andriacchi, 1998) are the current standard for motion capture in biomechanical applications. Therefore, the purpose of this study was to compare JC locations during gait using markerless and marker-based motion capture techniques.